Keberhasilan Pengobatan Massal Filariasis di Kecamatan Kusan Hulu Kabupaten Tanah Bumbu Provinsi Kalimantan Selatan - Dian Eka Setyaningtyas; Windy Tri Yuana; Nita Rahayu (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2017)
Kusan Hulu Sub-district is one of filariasis endemic areas in Tanah Bumbu District of South Kalimantan Province which has implemented partial Mass Drug Administration (MDA) filariasis program starting in 2012 and simultaneously in all area of Tanah Bumbu District starting in 2015. This study aims to determine endemicity filariasis after the first MDA in 2015 in Kusan Hulu Sub-district by conducting a finger blood survey to determine microfilaria rate and know the type of microfilariae. The design of this study was cross sectional. The study was conducted in Kusan Hulu sub-district from March to November 2015. The results of the finger blood survey showed a mf rate of 0.4% of the 500 population. The type of microfilariae found was Brugia malayi. Both positive patients were of male sex with age> 45 years. There was a decrease in mf rate in Kusan Hulu Sub-district from before MDA compared to after the first MDA was conducted from 12.37% in 2008, and 0.91% in 2011 to 0.4% in 2015, so the area became nonendemic (mf rate <1%).